ATRA influences the differentiation and fusion of myoblasts by regulating Rarα/Pitx2, leading to abnormal development of the pelvic floor muscles (PFMs) in fetal rats - Hanbin Zhao; Jian Cao; Huaqi Mu; Yang Bi; Zhenhua Guo; Yuan Shi; Yi Wang (PLoS ONE, 2026)
Anorectal malformation (ARM) is the most common congenital digestive tract anomaly in newborns, and children with ARM often have varying degrees of underdevelopment of the pelvic floor muscles (PFMs). To explore the effects of Rarα (NR1B1) and Pitx2 on the development of rat PFMs, we constructed a rat ARM animal model using all-trans retinoic acid (ATRA), and verified the expression of Rarα and Pitx2 in the PFMs of fetal rats. Additionally, we used rat myoblasts (L6 cells) to investigate the regulatory roles of Rarα and Pitx2 in skeletal muscle myoblast differentiation and their interactions. The results indicated a significant decrease in the expression of Rarα and Pitx2 in the PFMs of fetal rats with ARM. ATRA can also decrease the expression of Rarα and Pitx2 in the L6 cells, while affecting the differentiation and fusion of L6 cells. Knocking down Rarα in L6 cells reduced the expression of Pitx2, Myod1, Mymk, and decreased myogenic activity in L6 cells. When Rarα is activated, the decreased expression of Pitx2, Myod1, and Mymk and myogenic differentiation can be restored to different extents. At the same time, increasing or inhibiting the expression of Pitx2 can counteract the effects of knocking down Rarα and activating Rarα respectively. These results indicate that Pitx2 may be downstream of the transcription factor Rarα, mediating the effects of ATRA on the development of fetal rat PFMs.